IB - Pacione, Michael (ed.) (London, 1981)
Growing concern for the future of cities and for the wellbeing of city dwellers, stimulated by trends in world urbanisation, the increasing number and size of cities, and the deterioration of many urban environ ments, has led in recent years to much emphasis being placed upon the applied or problem-solving approach to the study of the city. The importance of this viewpoint has been widely recognised. The conse quent scale and pace of developments in applied urban geography and related fields has inevitably diminished the relevance and usefulness of many standard urban texts. Much of the material that is available on urban problems and planning is now outdated or is restricted in its geographical coverage. These deficiencies were highlighted during the preparation of a series of undergraduate lectures on urban geography and planning. It soon became evident that lecturers, students and others interested in urban problems and planning in the modern world must be prepared to expend considerable time and energy scouring less access ible reports and numerous academic journals across several disciplines in order to obtain satisfactory detailed information. This book, together with the companion volume on Urban Problems and Planning in the Developed World, attempts to offset some of these deficiencies by providing a collection of discussions on the problems and planning activities in a number of cities selected to reflect the differing economic, cultural and political regimes of the modern world.
Keywords: Developing countries-City planning